The Modify Version of Artificial Bee Colony Algorithm to solve Real Optimization problems - B. Asady; Parvaneh Mansouri; N. Gupta (Institute of Advanced Engineering and Science, 2012)
The Artificial Bee Colony(ABC) algorithm is one of the best applicableoptimization algorithm. In this work, we make some modifications toimprove the ABC algorithm based on convergence speed of solution. Inorder to, we add some conditions to selected food sources by bees. So, ifsolution have been enough near to optimal solution, then further search existaround the food sources. That, this is near to optimal solution because, wecan replace lower and upper bounds of food sources with smaller valuesrelate to last search. Therefore, the new search is near to optimal solution and after some iteration, optimal solution achieves. Finally, we illustrateconvergence speed of the MABC algorithm that is faster than ABCalgorithm. There are some examples.DOI:http://dx.doi.org/10.11591/ijece.v2i4.423